Analisis Strategi Pemasaran Pada Usaha Bakso Booming Di Kota Makassar - Riu, Isma Azis (Journal Management & Economics Review (JUMPER), 2024)
Micro small medium enterprise is a type of business with a relatively small scale. Similar to performance, the performance of micro, small and medium enterprises reflects the work results achieved in accordance with the duties and responsibilities carried out in an effort to achieve goals. The purpose of writing this scientific article is to present an analysis of the marketing strategy of the Bakso Booming 88 business in the city of Makassar on the performance of micro, small and medium enterprises. Observations, interviews and documentation are used to collect data which will be analyzed using a qualitative descriptive method. The results of this study indicate that the right strategies that can be used to increase sales at "Meatballs Booming" SMEs are: SWOT strategy: increase promotional media, increase the number of Frozen Food products, use various goods delivery services, actively carry out promotions with the principle "don't be afraid of getting fat". to increase consumer interest to buy.